A Combined Energy and Geoengineering Optimization Model (CEAGOM) for climate and energy policy analysis. (15th May 2018) - Anasis, John G.; Khalil, Mohammad Aslam Khan; Butenhoff, Christopher; Bluffstone, Randall; Lendaris, George G.
Highlights: An energy optimization model incorporating geoengineering is described. The model employs commercial software and runs quickly. Model results compare well with a similar US government analysis. The model can be of use to policy-makers, researchers, and students. Abstract: Addressing greenhouse gas emissions and the associated global temperature rise will be one of the key issues of the 21st century. The supply and use of energy is the single largest contributor to anthropogenic greenhouse gas emissions through the burning of fossil fuels. Given the role fossil fuel use plays in the global economy, curtailing their use in order to mitigate climate change will be very difficult. This has led to proposals to deploy various types of geoengineering as a means of mitigating the global temperature increase. Current integrated assessment models (IAMs) do not readily incorporate geoengineering options. They are also complex to set up and run. This has led the authors to develop the Combined Energy and Geoengineering Optimization Model (CEAGOM) © . CEAGOM provides an easy to use software platform that explicitly includes geoengineering as potential options as part of the optimization of the energy resource mix for meeting a specified energy demand while still meeting specified climate targets. This paper describes the CEAGOM model and shows that its results compare quite favorably with those from a more complex IAM.